Outcomes of intentionally replanted molars according to preoperative locations of periapical lesions and the teeth - WooCheol Lee; Won-Jun Shon; Seung-Ho Baek; Kee-Yeon Kum; Hyeon-Cheol Kim (Elsevier, 2012)
Background/purpose: The aims of this retrospective study were to assess the influence of preoperative periapical lesions on the healing of intentionally replanted teeth and compare outcomes of intentional replantation (IR) between maxillary and mandibular molars. Materials and methods: In this study, we retrospectively analyzed 79 cases in whom the IR procedure was used. The outcome of treatment was classified clinically and radiographically as either success or failure. Results: The overall success rate of the reviewed IR procedures was 68.7%. The success rate of IR with mandibular molars (78.0%) was significantly higher than that with maxillary molars (41.2%). There was no significant difference between success rates of IR for teeth with and without preoperative periapical lesions (66.7% vs. 72.0%, respectively). Conclusions: Within the limitations of this study, IR of mandibular molars seemed to provide a higher success rate than that for maxillary molars, regardless of the presence of preoperative periapical lesions.